Measurement of the D*(2010)+ meson width and the D*(2010)+ - D0 mass difference - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2013)
We measure the mass difference Δm0 between the D∗(2010)+ and the D0 and the natural linewidth Γ of the transition D∗(2010)+→D0π+. The data were recorded with the BABAR detector at center-of-mass energies at and near the Υ(4S) resonance, and correspond to an integrated luminosity of approximately 477 fb−1. The D0 is reconstructed in the decay modes D0→K−π+ and D0→K−π+π−π+. For the decay mode D0→K−π+ we obtain Γ=(83.4±1.7±1.5) keV and Δm0=(145425.6±0.6±1.8) keV, where the quoted errors are statistical and systematic, respectively. For the D0→K−π+π−π+ mode we obtain Γ=(83.2±1.5±2.6) keV and Δm0=(145426.6±0.5±2.0) keV. The combined measurements yield Γ=(83.3±1.2±1.4) keV and Δm0=(145425.9±0.4±1.7) keV; the width is a factor of approximately 12 times more precise than the previous value, while the mass difference is a factor of approximately 6 times more precise.
Im Titel ist das Pluszeichen "+", der Stern "*" und die Zahl "0" hochgestellt
A Erratum to this article was published on 16 October 2013
Gesehen am 16.11.2021